2012
DOI: 10.1051/0004-6361/201118489
|View full text |Cite
|
Sign up to set email alerts
|

Spectral monitoring of RX J1856.5-3754 withXMM-Newton

Abstract: Using a large set of XMM-Newton observations, we searched for the long-term spectral and flux variability of the isolated neutron star RX J1856.5-3754 in the time interval from April 2002 to October 2011. This is the brightest and most extensively observed source of a small group of nearby, thermally emitting isolated neutron stars, of which at least one member (RX J0720.4-3125) has shown long-term variability. A detailed analysis of the data obtained with the EPIC-pn camera in the 0.15−1.2 keV energy range re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 32 publications
4
44
0
Order By: Relevance
“…The value of the radius is also in agreement with the estimates derived by Sartore et al (2012) and Ho et al (2007), assuming a source distance of 120 pc (Walter et al 2010). This choice translates into a gravitational red-shift factor at the star surface 1 + z = 1.26.…”
Section: The Model For Rx J1856supporting
confidence: 88%
See 1 more Smart Citation
“…The value of the radius is also in agreement with the estimates derived by Sartore et al (2012) and Ho et al (2007), assuming a source distance of 120 pc (Walter et al 2010). This choice translates into a gravitational red-shift factor at the star surface 1 + z = 1.26.…”
Section: The Model For Rx J1856supporting
confidence: 88%
“…However, taken face value, the previous expression for T dip yields vanishingly small values near the magnetic equator. The analysis of Sartore et al (2012) has shown that the X-ray spectrum of RX J1856 is best modeled in terms of two blackbody components with kT hand side should be a matrix, and B.12, where cos 2 θ k − sin 2 θ k should be cos 2 θ k + sin 2 θ k = 1. Figure 3 for the condensed surface.…”
Section: The Model For Rx J1856mentioning
confidence: 99%
“…This is because, once it is fixed, together with the Tolman-Oppenheimer-Volkoff (TOV) equation [43,44], we can obtain the so-called M−R relation [45], linking the neutron-star mass M and its radius R, which also gives the upper limit of the neutron-star mass. However, the determination of the EoS by astronomical observations is difficult, because even the known nearest neutron star (RX J1856.5-3754) is about 400 lightyears away from Earth [46]. Although neutron skins [47,48] and hallows [49,50] in neutronrich nuclei give information about neutron matter, it is still not enough to construct the neutron-star EoS, including the many-body effects associated with a strong neutron-neutron interaction [33].…”
Section: Introductionmentioning
confidence: 99%
“…Observations of this source were repeated with Xray satellites after ROSAT (e.g. Burwitz et al 2003, Beuermann et al 2006, Sartore et al 2012 not only for science purpose but also for calibration purpose. The latter is due to the fact that the X-ray spectrum of J1856 is ideal for instrumental calibration in soft X-ray range (e.g.…”
Section: Introductionmentioning
confidence: 99%